1986
DOI: 10.1017/s002185960006189x
|View full text |Cite
|
Sign up to set email alerts
|

Relative efficiency of prilled urea, urea supergranules (USG) and USG coated with neem cake or DCD for direct-seeded rice

Abstract: SUMMARYA field experiment was made during the rainy season of 1982 and 1983 at the Indian Agricultural Research Institute, New Delhi to study the relative efficiency of prilled urea, urea supergranules (USG) and USG coated with neem cake and DCD. Prilledurea was applied at 60, 120 and 180 kg N/ha, while the other sources of N were applied only at 120 kg N/ha. Nitrogen was added to rice in a single application 20 days after sowing (20 DAS) or in two applications, half 20 DAS and the rest at panicle initiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

1987
1987
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…The nitrification of urea-N was probably slowed by DCD thus conserving much of the applied N over winter. Sudhakara and Prasad (1986) found that coating large urea granules with DCD improved the response of rice although to a lesser extent than in this study.…”
Section: Discussioncontrasting
confidence: 61%
“…The nitrification of urea-N was probably slowed by DCD thus conserving much of the applied N over winter. Sudhakara and Prasad (1986) found that coating large urea granules with DCD improved the response of rice although to a lesser extent than in this study.…”
Section: Discussioncontrasting
confidence: 61%
“…1). Beneficial effects of N application on yield attributes have been reported by several workers (SHARMA and PRASAD 1980, SUDHAKARA and PRASAD 1986.…”
Section: Resultsmentioning
confidence: 73%
“…Sulphur coated urea (SCU) and neem coated urea (NCU) were no better than prilled urea. SUDHAKARA and PRASAD (1986) have also reported the advantage of a nitrification inhibitor DCD and of USG for direct-seeded rice in respect of panicle weight, b) Grain and straw yield of rice: Nitrogen application upto 300 kg/ha significantly increased grain and straw yield of direct seeded rice (Fig. 1), the difference between each successive level studied were significant.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Prasad et al (1970) reported that N losses through leaching could be minimized by increasing the size of the N fertilizer granules or by coating urea with nitrification-retarding chemicals or such materials as sulphur and neem cake. Such coated fertilizers and large granules have increased the efficiency of N uptake of several other crops (Sudhakara & Prasad 1986;Ram et al 1988) and allowed economies of N use in succeeding crops by leaving large residues of fertilizer N (Singh & Singh 1986). Such information is lacking for sugarcane.…”
Section: Introductionmentioning
confidence: 99%